2009
DOI: 10.1128/iai.00176-09
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusInduces Microglial Inflammation via a Glycogen Synthase Kinase 3β-Regulated Pathway

Abstract: A proinflammatory role for glycogen synthase kinase 3␤ (GSK-3␤) has been demonstrated. Here, we addressed its roles on heat-inactivated Staphylococcus aureus-induced microglial inflammation. Heat-inactivated S. aureus induced tumor necrosis factor alpha (TNF-␣) and nitric oxide (NO) production, at least in part, via a Toll-like receptor 2-regulated pathway. Neutralization of TNF-␣ largely blocked heat-inactivated S. aureus-induced NO. Heat-inactivated S. aureus activated GSK-3␤, and inhibiting GSK-3␤ reduced T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…This inactivation can be exerted by several kinases, including PKA, Akt (protein kinase B, which has been confirmed a downstream effector for Epac in macrophage), some isoforms of protein kinase C, and so on (Dugo et al 2007). Recently, several investigations have observed that inhibiting GSK-3β reduced TNF-α production in heat-inactivated Staphylococcus aureusinduced microglia (Cheng et al 2009), and GSK-3-inhibitor treatment increased IL-10 expression in LPS-stimulated microglia ). In combination with these results, our data indicated that inactivation of GSK-3β might implicate in the Epac's inhibitory effect of on TNF-α and in the PKA's suppressive effect on TNF-α and positive effect on IL-10.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This inactivation can be exerted by several kinases, including PKA, Akt (protein kinase B, which has been confirmed a downstream effector for Epac in macrophage), some isoforms of protein kinase C, and so on (Dugo et al 2007). Recently, several investigations have observed that inhibiting GSK-3β reduced TNF-α production in heat-inactivated Staphylococcus aureusinduced microglia (Cheng et al 2009), and GSK-3-inhibitor treatment increased IL-10 expression in LPS-stimulated microglia ). In combination with these results, our data indicated that inactivation of GSK-3β might implicate in the Epac's inhibitory effect of on TNF-α and in the PKA's suppressive effect on TNF-α and positive effect on IL-10.…”
Section: Discussionmentioning
confidence: 97%
“…Although actions of cAMP have been suggested mainly through protein kinase A (PKA) and a novel target named cAMP-responsive guanine nucleotide exchange factor (Epac) in macrophage (Aronoff et al 2005), the respective roles of PKA vs Epac in the anti-inflammatory effect of cAMP are still obscure in microglia. Furthermore, several signaling molecules such as mitogen-activated protein kinases (MAPK) p38 and glycogen synthase kinase-3β (GSK-3β), which are important for regulating cytokines production in microglia (Bhat et al 1998;Cheng et al 2009;Huang et al 2009), have been considered as plausible downstream effectors regulated by cAMP signaling (Jing et al 2004;Woo et al 2003), but the relationship between influence of PKA and Epac on these kinases with cytokines expression is still incompletely defined.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, phosphorylation of GSK-3 by Akt turns off its catalytic activity, resulting in the activation of pathways that are normally repressed by GSK-3 (15). In this context, Cheng et al (18) reported that inhibition of GSK-3␤ blocks NF-B activation, TNF-␣ production, and iNOS/NO biosynthesis but increases IL-10 production when the microglia is stimulated with heatinactivated S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies using different bacteria or bacterial virulence factors have documented the activation of the PI3K-Akt signaling pathway (3,7,20,30,33,38,50,60), NF-B (18,20,30,38), and more recently GSK-3 (11,18,43,44), none of them has reported the participation of the PI3K-Akt signaling pathway in the internalization of S. aureus. We have recently demonstrated that internalization of S. aureus by bovine endothelial cells (BEC) was increased by the soluble proinflammatory cytokines tumor necrosis factor alpha (TNF-␣) and interleukin-1␤ (IL-1␤) through a process associated with the NF-B activity state (47).…”
Section: Aureus Triggered a Time-dependent Phosphorylation Of Glycogementioning
confidence: 99%
“…GSK-3b is also involved in activating NF-jB in response to inflammatory stimuli and GSK-3b inhibitors have been widely used to reduce microglial inflammation and neurotoxicity (Hoeflich et al 2000;Takada et al 2004;Dugo et al 2007;Huang et al 2009;Yuskaitis and Jope 2009). Recent studies have reported that inhibiting GSK-3b blocks NF-jB activation, TNF-a production, and iNOS/NO biosynthesis in heat inactivated Staphylococcus aureusstimulated microglia (Cheng et al 2009). The interaction between b-catenin and GSK-3b associated with glutamateinduced neurotoxicity in rat hippocampus has been reported (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 96%